Towards a unified theory of happiness: Nozick versus Haybron - Piller, Christian (Voluntas: Revista Internacional de Filosofia, 2025)
In this paper, I present a puzzle, an inconsistent triad of claims, pertaining to common views about the nature and significance of happiness. I argue that viewing happiness as an emotion helps us to resolve this puzzle by introducing conditions of when which emotions are appropriate. I reject Haybron’s view that our notion of happiness is ambiguous, and I side with Nozick on how to combine different elements in a unified theory of happiness. I point out that unification at the semantic level leaves other issues open.